Analysis Of Learning Skills In Viewing Children's Drama Titled "Malin Kundang" In Students Of Class Phase C - Lusy Yuniastuti; Cerianing Putri Pratiwi; Heny Kusuma Widyaningrum (International Journal of Technology and Education Research, 2025)
This study aims to analyze the viewing skills of the children's drama performance "Malin Kundang," performed by 5th and 6th-grade students of SDIT Tunas Cendekia through a video uploaded on the YouTube platform. The method used in this research is descriptive qualitative, assessing various aspects of the drama performance, namely expression and emotion, lip synchronization, role immersion, cooperation among actors, as well as stage and property utilization. The results show that most of the actors have been able to deliver good performances, especially in the aspects of role immersion and property utilization. However, some shortcomings were still found, such as less harmonious cooperation among actors and insufficient depth of expression in some actors. The analysis also indicates that understanding the character and collaboration among actors play an important role in improving the quality of the performance. With more intensive guidance and training, it is expected that the quality of children's drama performances can be improved comprehensively. This research is expected to contribute to the development of more effective drama-based learning strategies and to enhance elementary school students' drama viewing skills through visual media.